SEJARAH PERADABAN EKONOMI ISLAM DI MALAYSIA - Nur Amalia, Gina; Irfan Saefuloh (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2021)
Malaysia is one of the countries in Southeast Asia that is quite advanced in its Islamic economic development, compared to other Southeast Asian countries. As a country that is very close both geographically, historically and culturally, Muslims in Indonesia need to know the historical journey of Islamic economic civilization in Malaysia in the context of comparative studies. With a complete regulatory infrastructure and support from the government, Malaysia can be said to have succeeded in making Islamic finance a branding at the global level. The country has successfully developed a market share of Islamic banking reaching around 24% for 30 years. The approach in this study uses literature studies from various references in the form of books and scientific articles related to the history of Islamic economic civilization in Malaysia. Malaysia adalah salah satu Negara di kawasan Asia Tenggara yang cukup maju dalam perkembangan ekonomi Islam, dibandingkan dengan Negara-negara Asia Tenggara yang lain. Sebagai sebuah Negara yang amat dekat baik secara geografis, historis, dan kultural, umat Islam di Indonesia perlu mengetahui perjalanan sejarah peradaban ekonomi Islam di Malaysia dalam rangka studi komparasi. Dengan infrastruktur regulasi yang lengkap dan dukungan dari pemerintah, Malaysia dapat dikatakan sukses menjadikan Islamic finance sebagai Branding dalam tataran global. Negara tersebut sukses mengembangkan market share perbankan syariah mencapai sekitar 24% selama 30 tahun. Pendekatan dalam kajian ini menggunakan studi kepustakaan dari berbagai referensi berupa buku dan artikel ilmiah yang berkaitan dengan sejarah peradaban ekonomi Islam di Malaysia.